An organic semiconductor as an anode-buffer for the improvement of small molecular photovoltaic cells. Issue 61 (3rd August 2017) - Wang, Lu; Li, Xin; Tan, Tian Wen; Shi, Ying; Zhao, Xin Yan; Mi, Bao Xiu; Gao, Zhi Qiang
Abstract : Organic semiconductor based anode buffer layers (ABLs) were studied. The physical and electrical properties of the device were investigated. Abstract : A hole transport material, 1, 3, 4, 5, 6, 7-hexaphenyl-2-{3′-(9-ethylcarbazolyl)}-isoindole (HPCzI), was used to serve as an efficient organic anode-buffer for organic photovoltaic cells (OPVs) with a bulk heterojunction structure comprising a copper phthalocyanine (CuPc) and fullerene (C60) mixture. Compared with a CuPc or molybdenum trioxide (MoO3 ) anode-buffer layer, the HPCzI based OPV device exhibits improved performance. Due to its highest occupied molecular orbital (HOMO) energy level being well matched with ITO and its relatively high hole conductivity, HPCzI can facilitate hole-extraction and reduce device resistance, leading to a significantly improved fill factor (FF) in the OPV device. Furthermore, when HPCzI was doped with MoO3, additional promotion of the device performance was achieved, which is supposedly attributed to the increase of the hole transport ability in an anode-buffer interface and better ohmic contact with ITO.